Django Reinhardt’s solo on Flèche d’Or (Per Musi, 2014)
Transcription and analysis of Django Reinhardt’s solo on his own composition, Flèche d’Or. The structural and harmonic aspects of this work, recorded in 1952, show great similarities with Milestones (1958) by Miles Davis, a well-known work generally accepted as the first example of the so called modal jazz. This article also presents a transcription of the accents and displaced rhythms performed by the drummer Pierre Lemarchand, in order to demonstrate a measure mistake that could be caused by the recent novelty of this kind of musical form in jazz. The analysis of the solo reveals an “outside” approach by Django as far as the harmony and rhythm are concerned.